2013
DOI: 10.1186/1756-3305-6-44
|View full text |Cite
|
Sign up to set email alerts
|

Blood meal origins and insecticide susceptibility of Anopheles arabiensis from Chano in South-West Ethiopia

Abstract: BackgroundAnopheles arabiensis, the main malaria vector in Ethiopia, shows both anthropophilic and zoophilic behaviours. Insecticide resistance is increasing, and alternative methods of vector control are needed. The objectives of this study were to determine the blood meal origins and the susceptibility to insecticides of An. arabiensis from Chano village near Arba Minch in South-West Ethiopia.MethodsBlood meal sources of anopheline mosquitoes collected using Centers for Disease Control and Prevention (CDC) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
74
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 50 publications
(75 reference statements)
13
74
2
Order By: Relevance
“…arabiensis showed zoophilic and an exophilic tendency, which is in harmony with what was documented before [21]. The preference of An.arabiensis to feed on cattle and rest outside after feeding in this study strengthens the findings of the study in Chalo of Southern Ethiopia, 65 km away from the current study area [31]. The experimental study in Tanzania also confirmed its tendency to escape from houses after feeding [32].…”
Section: Discussionsupporting
confidence: 90%
“…arabiensis showed zoophilic and an exophilic tendency, which is in harmony with what was documented before [21]. The preference of An.arabiensis to feed on cattle and rest outside after feeding in this study strengthens the findings of the study in Chalo of Southern Ethiopia, 65 km away from the current study area [31]. The experimental study in Tanzania also confirmed its tendency to escape from houses after feeding [32].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the insecticide tested is identical to those used for mosquito control indoors and subject to increasing levels of resistance [45]. Accordingly, treating cattle for mosquito control with pyrethroids is unlikely to be sustainable and frequent application would contribute to even more rapid development of resistance [46]. Already, deltamethrin resistance of An.…”
Section: Discussionmentioning
confidence: 99%
“…Research into long-lasting formulations persisting at least for 1 month would be desirable. However, given that pyrethroids are the only class of insecticide currently licensed to treat mosquito nets, and the increasing resistance of malaria vectors against pyrethroids insecticides [45], it would be wise to investigate alternatives with a completely different mode of action [9, 46]. Our entomological sampling with CBTs highlights that targeting cattle for mosquito control has potential.…”
Section: Discussionmentioning
confidence: 99%
“…Anopheles arabiensis has developed resistance to the pyrethroid insecticides and DDT, and showed a greater tendency to feed on cattle than humans, with an overall human blood index (HBI; the proportion of the An. arabiensis fed on human blood meals of the total blood meals determined) of 44% and a bovine blood index of 69% 18. We report anopheline species diversity, monthly variations of An.…”
Section: Introductionmentioning
confidence: 92%